Synthesis and Hypoglycemic Activity of Some New Flavone Derivatives - Bozdağ, Oya; Verspohl, Eugen J; Ertan, Rahmiye (Arzneimittelforschung, 2000)
A new series of 3’-flavonyl-2,4-thiazolidinedione, 2,4-imidazolidinedione and 2-thiohydantoin derivatives (1-10) were synthesized and their chemical structures have been elucidated by various spectral data. The prepared compounds were tested for their insulinotropic effects in INS-1 cells. Inhibitory effects were observed for compounds 1 and 2. In contrast compounds 4, 7 and 8 were able to increase insulin release compared with glibenclamide.
Keywords: Antidiabetic agents; Diabetes mellitus, insulin secretion; Flavone derivatives 2,4-Thiazolidinediones